Assessment in clinical education: A comparison between a generic instrument and a course-specific criterion-based instrument. (December 2018) - Ulfvarson, Johanna; Oxelmark, Lena; Jirwe, Maria
Assessment of students' clinical performance and reasoning raises critical questions of whether learning outcomes have been reached and whether the aims of a course/education programme have been fulfilled. The aim of this study was to compare two assessment instruments in clinical education. A cross-sectional, comparative design was used. Nursing students and supervisors from five universities and university colleges in Sweden were included in the study. A sample of 435 students was used. Data were collected with study-specific questionnaires targeted for the two groups, nursing students and supervisors, and were analysed using cross-tabulation, chi-square with WinSTAT. Students perceived supervisors using the instrument Assessment of Clinical Education (AClEd) to be more aware of what to assess and they experienced more support from the 'AClEd supervisors' as compared to the supervisors using the second instrument, the Assessment form for Clinical education (AssCe). Furthermore, the AClEd assessment was perceived to be fairer compared to the AssCe assessment. The criterion-referenced assessment instrument AClEd was perceived, by both nursing students and supervisors, to give a clearer view of the learning outcome and the possibility of a fair and comprehensive assessment.